Determinan yang Berhubungan dengan Risiko Depresi pada Lansia - Azhar Mualim; Syarifah Rauzatul Jannah; Hilman Syarif; Asniar Asniar; Zurnila Marli Kesuma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the determinants associated with the risk of depression in the elderly in Muara Tiga District, Pidie Regency. The method used is quantitative research with an analytical survey approach. A total of 79 elderly by accidental sampling were involved as respondents in this study. The results showed that the p-value between family role factors, family function and family support with the risk of depression in the elderly was 0.000. The multivariate test results using ordinal logistic regression analysis showed that the role of family factors was most dominantly related to the risk of depression in the elderly because the p-value closest to the alpha value was 0.163. In conclusion, there is a relationship between family roles, family functions and family support with the risk of depression in the elderly. Keywords: Family Support, Family Function, Elderly, Family Role, Depression Risk